18 One Page User Friendly Proforma Delivers Dramatic Improvements in Heart Failure Management in a Busy District General Hospital. (3rd June 2016) - Coyle, Clare; Nyathi, Baltazar; Woldman, Simon; Sanghvi, Mihir; Iles, Lindsey; Gupta, Sandy; Das, Debashish
Abstract : Background: Heart failure affects almost one million people in the UK with survival rates comparable to or worse than many cancers. Recent publications of the NICOR National Heart Failure Audit have focused attention on the need for improvement. This challenge is particularly acute in busy district general hospitals in London such as Whipps Cross University Hospital. Objective: We aimed to investigate if the implementation of a simple one-page user friendly Whipps Cross Heart Failure Improvement Proforma- the 'WHIP form' in all medical wards could help improve the management of patients admitted with heart failure against standard quality measures. Methods: The 'WHIP form' was introduced and implemented in all medical wards supported with a one-day educational seminar and a new dedicated heart failure email service. Results: Between June to September 2015, 106 patients with a primary admission diagnosis of heart failure were enrolled and managed using the 'WHIP form'. Inpatient mortality remained stable at 11.3% with an average hospital stay of 13.5 days. The 30-day readmission rate halved from 14% to 7%. Patients with documented left ventricular systolic dysfunction on Echocardiogram had significant improvements in the prescription of prognostic medication on discharge: ACEi/ARBs prescription increased from 78% from 88% [10% improvement]. B-Blockers prescription increased from 68% to 95% [27% improvement]. Conclusion: The initiation of an "easy to use" one page heart failure management proforma led to a dramatic reduction in 30-day readmission rates and significant increase in the prescription of prognostically important ACE inhibitors and B-blockers. If the reductions in 30-day readmissions are sustained, we estimate that our cost neutral intervention could translate to yearly savings of nearly £80K for Whipps Cross University Hospital alone.